An Experimental Study on the Influence of Tibetan Antelope Conservation Documentary on Audience. Issue 1 (November 2020) - Li, Yuwei; Yang, Bai
Abstract: From the perspective of human activities, survival and development, the documentary on the protection of Tibetan antelope reveals the current situation of the survival crisis of rare and wild Tibetan antelope, and shows the panoramic ecology of the competition between hunters and guardians. This paper uses text analysis, narrative analysis and experimental research methods to explore the ecological view of Tibetan Buddhism reflected in the Tibetan antelope conservation documentary, presents the image creation techniques used by the ecological view and the environmental action force generated by the audience. Through text analysis and research, recorded images show the natural and environmental protection concepts of "all living creatures have spirits" in Tibetan Buddhism, such as worship of nature, protection of life extension, equality of all living beings, prevention of killing and protecting living creatures. It is not difficult to draw the conclusion that the documentary image is based on the premise of non-fiction, and the image theme containing the ecological ethics of Tibetan Buddhism is expressed by means of symbolic narration and detailed narration. Through the experimental research method, combined with the questionnaire survey contents of the experimental subjects, some readers and listeners will increase the awareness of ecological protection and generate the power of environmental action.